2004
DOI: 10.2108/zsj.21.417
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Types of Cytochrome P450 Aromatase in the Serial-sex Changing Gobiid Fish, Trimma okinawae

Abstract: -To investigate the role of estrogen in the serial-sex changing fish Trimma okinawae , we isolated complementary DNAs encoding two distinct cytochrome P450 aromatase isoforms from adult ovary and brain (termed P450aromA and P450aromB, respectively). Sequence and phylogenic analyses showed that the goby P450arom forms belong to two separate CYP19 subfamilies. Transient expression of these cDNAs in HEK293 cells caused conversion of exogenous testosterone to estradiol-17 b . RT-PCR showed that P450aromA was expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 37 publications
5
20
0
Order By: Relevance
“…The similar patterns of cyp19a1a expression during oogenesis were also observed in red seabream (Gen et al 2001) and gobiid fish (Kobayashi et al 2004). The increase of ovarian cyp19a1a expression during vitellogenesis is in agreement with the role of gonadal estrogen in stimulating the hepatic synthesis of vitellogenin in teleosts (Nagahama 1994).…”
Section: Discussionsupporting
confidence: 67%
“…The similar patterns of cyp19a1a expression during oogenesis were also observed in red seabream (Gen et al 2001) and gobiid fish (Kobayashi et al 2004). The increase of ovarian cyp19a1a expression during vitellogenesis is in agreement with the role of gonadal estrogen in stimulating the hepatic synthesis of vitellogenin in teleosts (Nagahama 1994).…”
Section: Discussionsupporting
confidence: 67%
“…In T. okinawae, the ovarian isoform mRNA was present in ovary and testis, and the ovarian isoform transcripts correlated with ovarian development, suggesting that the ovarian isoform, but not the brain isoform, is involved in the regulation of ovarian vitellogenesis in this species (Kobayashi et al 2004). Hence, if two aromatase isoforms are also present in G. erythrospilus, the results of our study suggest that fadrozole blocks the ovarian isoform in this species.…”
Section: Discussionmentioning
confidence: 52%
“…Our previous PCR results suggested that there was approximately 700 times less CYP19A1 expression in male gonads compared to females, and there was actually more CYP19A2 in testis than CYP19A1 (Patel et al, 2006). CYP19A1 expression was also reported in goby testis but the regulatory mechanisms or the physiological significance of aromatase in the male gonad is currently unknown (Kobayashi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Highest CYP19A1 mRNA expression was found in Stage III B zebrafish ovarian vitellogenic follicles (Goto- Kazeto et al, 2004;Rodriguez-Mari et al, 2005). Kobayashi and colleagues found CYP19A2 mRNA expression in goby thecal cells of previtellogenic follicles while the expression was more abundant in granulosa cells of vitellogenic follicles (Kobayashi et al, 2004). However, aromatase immunoreactivity was found in both cell types of female goby (Sunobe et al, 2005).…”
Section: Introductionmentioning
confidence: 99%